Nutrients and tobacco : short and long-term effects on brain and cognition in childhood and adolescence - Kafouri, Salomi (2011)
The brain undergoes rapid structural and functional changes during gestation and in the first two years of life. But brain development also continues throughout childhood and adolescence with cognitive abilities getting improved. Threats to the vulnerable Central Nervous System can have long-lasting effects throughout the foetal and neonatal periods and beyond infancy, on all aspects of development. This thesis investigates the long-term associations of prenatal tobacco exposure, as well as the long-term associations of breastfeeding with brain and cognitive development of adolescents. Further, it investigates the short-term effects of omega-3 supplementation on brain and cognition of school-aged children. These will be examined in order to identify solutions for optimal development, both at brain and cognitive level, for the new generation. The first study is entirely based on maternal cigarette smoking during pregnancy association with cognitive development of adolescents. This study found no differences on cognitive development of exposed and non-exposed adolescents when maternal education was held constant in the two groups. The two subsequently studies examined long-term associations of breastfeeding duration with brain and cognition of adolescents. These studies found that breastfeeding duration was positively linked to intelligence and brain structures, such as caudate nucleus, which is vulnerable to environmental influences during critical periods of brain development. Lastly, the omega-3 supplementation study found no differences between active and placebo group on cognition but found associations between omega-3 fatty acids and brain microstructure thus hypothesizing that higher intake of ω-3 fatty acids can alter concentrations of specific ω-6 fatty acids thus influencing membrane fluidity. As such, our findings suggest that in order to obtain optimal brain and cognitive development, we do not only need to discard toxins or employ nutrients during critical periods of rapid brain development but also take into account other environmental and genetic factors that play vital role in children‘s development.